Long-term analysis of clear-sky new particle formation events and nonevents in Hyytiälä - Dada, Lubna; Paasonen, Pauli; Nieminen, Tuomo; Mazon, Stephany Buenrostro; Kontkanen, Jenni; Peräkylä, Otso; Lehtipalo, Katrianne; Hussein, Tareq; Petäjä, Tuukka; Kerminen, Veli-Matti; Bäck, Jaana; Kulmala, Markku (COPERNICUS GESELLSCHAFT MBH, 2017)
New particle formation (NPF) events have been observed all around the world and are known to be a major source of atmospheric aerosol particles. Here we combine 20 years of observations in a boreal forest at the SMEAR II station (Station for Measuring Ecosystem-Atmosphere Relations) in Hyytiala, Finland, by building on previously accumulated knowledge and by focusing on clear-sky (non-cloudy) conditions. We first investigated the effect of cloudiness on NPF and then compared the NPF event and nonevent days during clear-sky conditions. In this comparison we considered, for example, the effects of calculated particle formation rates, condensation sink, trace gas concentrations and various meteorological quantities in discriminating NPF events from nonevents. The formation rate of 1.5 nm particles was calculated by using proxies for gaseous sulfuric acid and oxidized products of low volatile organic compounds, together with an empirical nucleation rate coefficient. As expected, our results indicate an increase in the frequency of NPF events under clear-sky conditions in comparison to cloudy ones. Also, focusing on clear-sky conditions enabled us to find a clear separation of many variables related to NPF. For instance, oxidized organic vapors showed a higher concentration during the clear-sky NPF event days, whereas the condensation sink (CS) and some trace gases had higher concentrations during the nonevent days. The calculated formation rate of 3 nm particles showed a notable difference between the NPF event and nonevent days during clear-sky conditions, especially in winter and spring. For springtime, we are able to find a threshold equation for the combined values of ambient temperature and CS, (CS (s(-1)) > -3.091 x 10(-5) x T (in Kelvin) + 0.0120), above which practically no clear-sky NPF event could be observed. Finally, we present a probability distribution for the frequency of NPF events at a specific CS and temperature. Peer reviewed